EFEK AIR LAUT, ZEOLIT DAN PASIR VULKAN TERHADAP SIFAT KIMIA TANAH GAMBUT - Firlana Firlana; Sarifudddin Sarifudddin; Kemala Sari Lubis (Universitas Sumatera Utara, 2013)
The objective of this research is to study the effect of sea water, zeolit, and volcanic material onchemical properties of peat soils. This research was conducted at green house, soil chemical andfertility laboratory and research laboratories and technology. This research used factorialrandomized block design with two (2) factors treatments consist of mineral materials (zeolite andvolcanic material) and sea water with three (3) replications. Zeolite and volcanic material were 200gram/pot and 1000 gram/pot. Volume of sea water were 500 ml (+ 1500 ml fresh water) per pot,1000 ml (+ 1000 ml fresh water) per pot dan 1500 ml (+ 500 ml fresh water) per pot. The resultsshowed that application of mineral zeolite and volcanic material influenced significantly increasedof soil acidicity, exchange kalium, exchange calsium, exchange magnesium, number of tillers perclump and number of productive tillers per clump. Volume of sea water influenced significantlyincrease of soil acidicity and electrical conductivity, number of tillers per clump and number ofproductive tillers per clump, but not significantly effect on cation exchange capacity and basesaturation.Keywords : zeolite, volcanic material, sea water, and peat soil